TRADISI RARAK GODANG “OGUANG” DALAM ADAT MELAYU PADA UPACARA PERNIKAHAN DI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - SRI WAHYU ILLAHI; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The purpose of this research is to find out the origin of the “oguang” rarak godang tradition, to find out the finctions and benefits, to find out the shift in the “oguang” godang rarak tradition in Malay at a wedding ceremony in Benai District. The “oguang” rarak godang tradition is a procession carried out jointly between 2 tribes and customary stakeholders, to parade the bride and from the bride’s hause to the bridal hause. The method that I use in this research is qualitative. From the research results it is known that the picture of the “oguang” rarak godang tradition has several functions. The first function is, 1. Tighten siluturrahmi rope. 2. Means of Communication. 3. Means of entertainment. 4. Means of sel-expression. 5. Symbol and parts of legality. 6. Enforcement of Community social norms. 7. To enliven a wedding. The significance of the “oguang” rarak godang tradition is part of the legality as well as the symbol or legitimate symbol of the only event for a wedding ceremony. In the “oguang” rarak godang tradition, 2 gongs and 1 drum are used which are played with beating with coconut and rattan midribs. This shift from tradition due to the lack of traditional musical instruments and the advencement of the times.Key Words: “Oguang” Rarak Godang